1992
DOI: 10.1007/bf00122063
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of turbulent fluxes of sensible heat and momentum in the surface boundary layer during the Indian summer monsoon

Abstract: Turbulent fluctuations of wind and temperature were measured using a three-component sonic anemometer at 8 m on a 30 m micro-meteorological tower erected at the Indian Institute of Technology (IIT) Kharagpur (22.3" N, 87.2" E), India, as part of the Monsoon Trough Boundary Layer Experiment (MONTBLEX). Diurnal and nocturnal variations of fluxes of sensible heat and momentum were estimated by the eddy correlation technique from 42 observations, each of 10 min duration during 6-8 July in the monsoon season of 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…1e-f )) and almost fall in line within the stability range from − 0.1 to 0.1 as noticed by Krishnan and Kunhikrishnan [14]. With instability, the w ∕u * increases and follow 1/3 power law as observed by previous studies [23,29]. The difference of present relationships from the relationships given in the literature is explaining the seasonal and site-specific characteristics of such relationships in the neutral region.…”
Section: Normalised Standard Deviation Of Wind Componentssupporting
confidence: 78%
See 1 more Smart Citation
“…1e-f )) and almost fall in line within the stability range from − 0.1 to 0.1 as noticed by Krishnan and Kunhikrishnan [14]. With instability, the w ∕u * increases and follow 1/3 power law as observed by previous studies [23,29]. The difference of present relationships from the relationships given in the literature is explaining the seasonal and site-specific characteristics of such relationships in the neutral region.…”
Section: Normalised Standard Deviation Of Wind Componentssupporting
confidence: 78%
“…[11,19]. The relationship of the normalised standard deviation of temperature ( T ∕T * ) and ζ has been reported by various researchers time to time over different regions [22,29,36].…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that the turbulent development of the CBL is affected by the surface heat flux (Avolio et al., 2017; Båserud et al., 2020; Maronga & Raasch, 2013; Sellers et al., 1995; Yi et al., 2001). The surface heat and momentum fluxes determine the intensity of the CBL turbulent diffusion, and the heat and water vapor flux also affect the formation of boundary layer clouds (Cava et al., 2006; Mahrt, 2000; Sivaramakrishnan et al., 1992; Su et al., 2018). Yi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Grossman and Durran (1984) studied the interaction between low-level flow observed during the Indian summer monsoon and the Western Ghats mountain range to examine the possible influence of complex topography on the intensification of offshore convection. Analysis by Sivaramakrishnan et al (1992) showed the importance of downward transport of momentum and sensible heat during the night-time under near-neutral stability. It was also shown that momentum transfer occurs in bursts, under the influence of large-scale circulations during monsoon conditions while the diurnal and seasonal variation of the monsoon LLJ has been studied by, e.g., Ardanuy (1979); Kalapureddy et al (2007); Nair et al (2014).…”
Section: Introductionmentioning
confidence: 99%